2009
DOI: 10.3892/or_00000331
|View full text |Cite
|
Sign up to set email alerts
|

Role of CCL5 in invasion, proliferation and proportion of CD44+/CD24− phenotype of MCF-7 cells and correlation of CCL5 and CCR5 expression with breast cancer progression

Abstract: Abstract. This study was undertaken to observe the effects and possible mechanism of CC chemokine ligand 5 (CCL5) on invasion, proliferation and percentage of CD44 + /CD24 IntroductionBreast cancer is a leading cause of death for women in many countries. The ability of breast cancer cells to metastasize to distal organs makes this disease refractory and incurable and is the vital factor contributing to the therapeutic effect and prognosis of breast cancer (1). The metastasis of cancer consisting of a series o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Parallel studies on CCL5 demonstrated its ability to induce small increases in breast tumor cell proliferation; in one of the research systems, such CCL5 activity was mediated by CCR5dependent mTOR activation (46)(47)(48). CCR5, a major CCL5 receptor, was targeted in several studies by maraviroc, leading to controversial results in terms of tumor cell proliferation (48)(49)(50)(51), which possibly reflect the use of different model systems and/or the ability of CCL5 to activate CCR1 and CCR3 in addition to CCR5.…”
Section: Atypical Chemokine Activities Exerted On Cancer Cells Tumor Cell Growth Survival and Senescencementioning
confidence: 99%
See 2 more Smart Citations
“…Parallel studies on CCL5 demonstrated its ability to induce small increases in breast tumor cell proliferation; in one of the research systems, such CCL5 activity was mediated by CCR5dependent mTOR activation (46)(47)(48). CCR5, a major CCL5 receptor, was targeted in several studies by maraviroc, leading to controversial results in terms of tumor cell proliferation (48)(49)(50)(51), which possibly reflect the use of different model systems and/or the ability of CCL5 to activate CCR1 and CCR3 in addition to CCR5.…”
Section: Atypical Chemokine Activities Exerted On Cancer Cells Tumor Cell Growth Survival and Senescencementioning
confidence: 99%
“…The two inflammatory CC chemokines, CCL2 and CCL5 were also found to elevate the generation of CSCs. This was evidenced by a CCL2-promoted formation of primary and secondary tumor spheroids that contained more self-renewing CSCs (82), and by the fact that stimulation of breast tumor cells with CCL5 increased the CD44 + /CD24 − sub-population (47). These CCL5-enriched CSCs expressed higher levels of the corresponding receptor CCR5 and were able to invade more than non-CSCs, ability that was abrogated by inhibition of CCR5 (47).…”
Section: Cancer Stem Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adipokines play a role in increasing the invasion of human and mouse breast cancer cells characterized by excessive expression of proteases, including proinflammatory cytokines (IL-6, IL-1β) and MMP-11 when co-cultured with adipocytes. Research shows that ADSCs increase the motility of MCF-7 breast cancer cells in vitro through the secretion of the chemokine CCL5 [13].…”
Section: Potential Evidence Of Adsc For Breast Reconstructionmentioning
confidence: 99%
“…Concurrently, multiple studies have established a connection between inflammation and cancer stem cells, with a particular emphasis on cytokines and chemokines. Treatment of breast cancer cell lines with Chemokine (C-C motif) ligand 5 (CCL5) leads to an enrichment of CD44 high /CD24l ow/-CSCs [10]. Chen et al identified CCL20 as an inflammatory factor that increases both ALDH+ and CD44 high /CD24l ow/-breast CSC frequencies in a population treated with taxanes [11].…”
Section: Introductionmentioning
confidence: 99%